Monetary-fiscal policies and stock market performance: evidence from linear ARDL framework - Emamian, Aref; Mazlan, Nur Syazwani (Global Academy of Training and Research (GATR) Enterprise, 2021)
Objective - To explore the impacts of monetary and fiscal policies, the appropriateness of both policies and how the stock market is affected by their adoption and implementation in the United States (US). Hence, this study aims to determine the short and long run relationships between monetary and fiscal policies and stock market performance as well as establish potential factors and policies contributing to the highs and lows.